1997
DOI: 10.1111/j.1151-2916.1997.tb02920.x
|View full text |Cite
|
Sign up to set email alerts
|

Young's Modulus, Flexural Strength, and Fracture of Yttria‐Stabilized Zirconia versus Temperature

Abstract: the mixture was hydrolyzed. The chemical route for powder The flexural strength and elastic modulus of cubic zirconia preparation, 1-3 scaleup to powder quantities of 400 kg, 4 and the that was stabilized with 6.5 mol% yttria was determined in specifics of billet fabrication 5 have been published previously. the temperature range of 25؇-1500؇C in air. Specimens wereThe calcined powders were used to fabricate dense ceramics diamond machined from both hot-pressed and sintered either by cold pressing and sinterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(81 citation statements)
references
References 12 publications
8
71
1
1
Order By: Relevance
“…Therefore, the characteristic martensitic transformation temperatures [16] are expected to determine the operating temperature window of shape memory ceramics [12], and lay the foundation for tailoring their high temperature shape memory properties [17]. More importantly, our earlier work suggested that the stress-induced transformation in small volume zirconia could exhibit a systematic monoclinic variant preference in terms of transformation crystallography [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the characteristic martensitic transformation temperatures [16] are expected to determine the operating temperature window of shape memory ceramics [12], and lay the foundation for tailoring their high temperature shape memory properties [17]. More importantly, our earlier work suggested that the stress-induced transformation in small volume zirconia could exhibit a systematic monoclinic variant preference in terms of transformation crystallography [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently we reported a new class of shape memory ceramics: micron-sized single-crystal zirconia [9]. These ceramics exhibit strains comparable to metals but have higher strength and potentially higher operating temperatures than metals [10,11] for applications like solid state actuators [12]. The microscale single crystal structure, characterized by a large surface area-to-volume ratio and absence of grain boundaries, helps to accommodate transformation-induced stress and thus eliminate cracks [13e15].…”
Section: Introductionmentioning
confidence: 99%
“…Although not presented here, it was also found that elastic modulus of the platelet composites was very close to that of the platelet composites. A similar transition at 400 °C was also observed in 6.5-YSZ by Adams et al [27]. Figure 15 shows elastic modulus as a function of alumina content for both particulate and platelet composites, determined at ambient temperature.…”
Section: Elastic Modulusmentioning
confidence: 49%
“…Therefore, the enhancement of mechanical properties of the solid electrolyte is an important problem to be solved [58][59][60][61].…”
Section: Zirconia -Baesed Electrolytesmentioning
confidence: 99%